The effectiveness of internal controls in preventing fraud in small and medium enterprises (SMEs) - Mohamad Zuki, Nur Iliya Zulaikha; Razak, Syuhaila (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Fraud frightens the long-term success and financial stability of Small and Medium Enterprises (SMEs) often causing financial losses and damage their reputation. Contrasting larger companies, SMEs often struggle to put in place full internal control systems because they lack resources, know-how, and limited regulatory oversight. This study explores at how well internal control methods work to prevent fraud in SMEs highlighting how important control measures are to protect financial integrity and work efficiency. It examines at weaknesses in SME internal controls, such as inadequate segregation of duties, weak checking processes, and lack of proper records. In addition, this research discusses strategies to mitigate these weaknesses, including the adoption of technology-driven controls, employee training programs, and periodic financial audits. Making internal controls stronger not cuts down fraud risks but also boosts how well the business runs and how tough it is in long-term. By sharing understandings on the best ways to prevent fraud, this study contributes to the existing body of knowledge on internal controls and offers practical recommendations for SME owners, managers, and policymakers in fostering a more secure business environment.